Beyond Glycemic Control: The Expanding Role of GLP-1 Analogues in Type 2 Diabetes and Metabolic Health - Mazur, Michał; Waz, Dorota; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła, Sebastian (Quality in Sport, 2024)
Introduction and Purpose: T2DM is a metabolic condition with significant global health implications, largely driven by aging populations and the obesity epidemic. Glucagon-like peptide-1 receptor agonists have transformed T2DM treatment by offering benefits that extend beyond blood glucose control, including weight reduction, cardiovascular protection, and potential effects on related metabolic conditions. This review aims to explore the mechanisms of GLP-1 RAs, their clinical applications, and their evolving role in addressing T2DM and its associated complications. Materials and Methods: The review is based on a detailed analysis of peer-reviewed studies from major scientific databases such as PubMed. The selected literature focuses on the mechanisms, clinical benefits, and new developments in GLP-1 RA therapies, including innovations in drug formulations and combination treatments. Results: GLP-1 RAs enhance glycemic control by stimulating glucose-dependent insulin secretion and suppressing glucagon release, with a low risk of hypoglycemia. They also facilitate significant weight loss by regulating appetite and slowing gastric emptying. Beyond these core effects, GLP-1 RAs reduce cardiovascular risks, slow the progression of chronic kidney disease, and show promise in managing NAFLD and neuroinflammation. Innovations such as dual and triple agonists and oral GLP-1 RA formulations have further expanded their therapeutic scope, improving patient outcomes and adherence. Conclusion: GLP-1 RAs represent a significant advancement in the management of T2DM and related metabolic disorders. By addressing interconnected issues such as glycemic control, weight management, and cardiovascular risk, these therapies play a central role in modern metabolic medicine. Ongoing research should focus on long-term outcomes, safety, and personalized approaches to maximize their full potential and accessibility.